The Effect of Cord Blood Vitamin D Level on Bronchopulmonary Dysplasia and Other Neonatal Morbidities in Preterm Infants - Elif Koc; Fatih Bolat; Meric Kaymak Cihan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: We aimed to investigate the relationship between cord 25-hydroxyvitamin D level and bronchopulmonary dysplasia and other neonatal morbidities (sepsis, necrotizing enterocolitis, intraventricular hemorrhage, patent ductus arteriosus, respiratory distress syndrome, retinopathy of prematurity) in preterm neonates.